ADVANTAGE OF STUDYING ABROAD (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ANNOTATION This article examines the advantages and obstacles of pursuing education overseas. Additionally, it offers advice for prospective students and outlines university admission requirements. Studying abroad is becoming more and moreappealing to students of various age groups. The benefits are numerous, ranging from exposure to a different culture and language acquisition to a broader global outlook. Nevertheless, challenges like expenses, language barriers, and cultural disparities arealso part of the studying abroad experience